PENGEMBANGAN MEDIA ELEKTRONIK “SI-BEBAS CAMKOD” UNTUK MENCEGAH CAMPUR KODE DALAM PEMBELAJARAN TEKS PIDATO SISWA SD - Anggia Nur Qolbi Hidayat; Dadan Djuanda; Enjang Yusuf Ali (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Code-mixing remains a persistent phenomenon in Indonesian language learning at the elementary school level, particularly in communities where local languages are used as the primary means of daily communication. This situation was also identified during speech text instruction in a fourth-grade classroom at SDN Sukaraja I Sumedang, where both teachers and students frequently inserted Sundanese vocabulary into classroom interactions, resulting in the inconsistent use of formal Indonesian. In response to this issue, this study developed the SI-BEBAS CAMKOD electronic learning media, which was designed to provide meaningful learning experiences while fostering the habitual use of formal Indonesian throughout the learning process. The media were developed using a Research and Development (R&D) approach based on the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. Data were collected through classroom observations, structured interviews, expert validation questionnaires completed by media and subject-matter experts, and student response questionnaires. The data were analyzed using descriptive qualitative and quantitative techniques. The developed product achieved feasibility scores of 88.8% from media experts and 88.3% from subject-matter experts, while student responses reached 89.2%, indicating a very good category. These findings indicate that the SI-BEBAS CAMKOD electronic learning media are feasible for use in speech text instruction at the elementary school level and have the potential to support the habituation of formal Indonesian through instructional materials, interactive learning activities, and a voice-recording feature. The findings confirm that SI-BEBAS CAMKOD is a feasible learning medium that integrates language instruction with the habituation of formal Indonesian use in the context of elementary school learning. ABSTRAK Fenomena campur kode masih mewarnai pembelajaran Bahasa Indonesia di sekolah dasar, terutama pada lingkungan yang masyarakatnya menggunakan bahasa daerah sebagai alat komunikasi sehari-hari. Situasi tersebut turut ditemukan dalam pembelajaran teks pidato di kelas IV SDN Sukaraja I Sumedang, ketika tuturan guru dan siswa masih diselingi kosakata bahasa Sunda sehingga penggunaan bahasa Indonesia formal belum berlangsung secara konsisten. Berangkat dari kondisi tersebut, penelitian ini mengembangkan media elektronik SI-BEBAS CAMKOD yang dirancang untuk menghadirkan pengalaman belajar sekaligus membiasakan penggunaan bahasa Indonesia formal selama proses pembelajaran. Pengembangan media dilaksanakan melalui pendekatan Research and Development menggunakan model ADDIE yang mencakup tahapan analisis, perancangan, pengembangan, implementasi, dan evaluasi. Informasi penelitian dihimpun melalui observasi, wawancara terstruktur, serta angket validasi ahli media, ahli materi, dan respons siswa, kemudian dianalisis secara deskriptif kualitatif dan kuantitatif. Produk yang dihasilkan memperoleh tingkat kelayakan sebesar 88,8% dari ahli media dan 88,3% dari ahli materi, sedangkan respons siswa mencapai 89,2% dengan kategori sangat baik. Hasil tersebut menunjukkan bahwa media SI-BEBAS CAMKOD layak digunakan dalam pembelajaran teks pidato di sekolah dasar serta berpotensi mendukung pembiasaan penggunaan bahasa Indonesia formal melalui penyajian materi, latihan interaktif, dan fitur rekam suara. Temuan tersebut menegaskan bahwa SI-BEBAS CAMKOD layak dimanfaatkan sebagai media pembelajaran yang mengintegrasikan materi kebahasaan dengan pembiasaan penggunaan bahasa Indonesia formal dalam konteks pembelajaran sekolah dasar.